Kesulitan, Penyebab, dan Solusi Belajar Berbicara Bahasa Indonesia Mahasiswa Pattani di Jambi: Sebuah Studi Kasus : Difficulties, Causes, and Solutions in Learning to Speak Indonesian Among Pattani Students in Jambi: A Case Study - Waedoyee, Asmee; Harjono, Hary Soedarto; Ningsih, Arum Gati; Samaeng, Rusnanee (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study examines the speaking difficulties experienced by Patani Southern Thailand students learning Indonesian in Jambi, Indonesia. Employing a qualitative case study design, this research identifies forms of speaking difficulties, analyzes causative factors, and describes coping strategies. Data were collected through observation, semi-structured interviews, and documentation from eight Patani students enrolled at universities in Jambi. The findings reveal that students face difficulties in vocabulary mastery, sentence construction, pronunciation, self-confidence, and first language Patani Malay interference. These challenges stem from cross-linguistic differences, limited practice opportunities, and unsupportive language environments. Effective coping strategies include participating in the Indonesian for Foreign Speakers (BIPA) program, engaging in regular speaking practice through diverse media, and creating a supportive Indonesian-speaking environment. This study contributes theoretically to BIPA scholarship, particularly regarding first language interference in speaking acquisition, and offers practical recommendations for universities and BIPA instructors in designing more contextual learning programs for Patani students.